2016
DOI: 10.1038/cddis.2016.313
|View full text |Cite
|
Sign up to set email alerts
|

XAB2 functions in mitotic cell cycle progression via transcriptional regulation of CENPE

Abstract: Xeroderma pigmentosum group A (XPA)-binding protein 2 (XAB2) is a multi-functional protein that plays critical role in processes including transcription, transcription-coupled DNA repair, pre-mRNA splicing, homologous recombination and mRNA export. Microarray analysis on gene expression in XAB2 knockdown cells reveals that many genes with significant change in expression function in mitotic cell cycle regulation. Fluorescence-activated cell scanner analysis confirmed XAB2 depletion led to cell arrest in G2/M p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 50 publications
0
43
0
Order By: Relevance
“…Depletion of XAB2 leads to defective NER. Previous ndings revealed that XAB2 is involved in the transcription-coupled sub-pathway of NER (TC-NER) 18,29 . To test for the functional role of XAB2 in NER, we carried a series of pulldown assays in nuclear extracts of UV-irradiated (10J/m 2 ) and control bXAB2 primary mouse embryonic broblasts (MEFs).…”
Section: Resultsmentioning
confidence: 99%
“…Depletion of XAB2 leads to defective NER. Previous ndings revealed that XAB2 is involved in the transcription-coupled sub-pathway of NER (TC-NER) 18,29 . To test for the functional role of XAB2 in NER, we carried a series of pulldown assays in nuclear extracts of UV-irradiated (10J/m 2 ) and control bXAB2 primary mouse embryonic broblasts (MEFs).…”
Section: Resultsmentioning
confidence: 99%
“…However, the role RRM2 plays in the development of cSCC is unclear. The protein encoded by CENPE is a forward-directed kinesin, belonging to the kinesin-7 subfamily, which is critical in mitosis [39]. Increasing evidence shows that CENPE may be a useful drug target for several tumors without targeted therapy [40].…”
Section: Discussionmentioning
confidence: 99%
“…CENPE is one of major spindle checkpoint genes and regulates the cell cycle. Down-regulation of CENPE leads to chromosome misalignment and delayed mitotic progression [29]. However, the clinical correlations and roles of CENPE in cancer are not quite clear at present.…”
Section: Discussionmentioning
confidence: 99%